2014
DOI: 10.1038/ejcn.2014.70
|View full text |Cite
|
Sign up to set email alerts
|

The value of Ret-Hb and sTfR in the diagnosis of iron depletion in healthy, young children

Abstract: Our results showed that the discriminative value of Ret-Hb and sTfR for the detection of iron depletion is limited. Our findings suggest that ferritin is the most useful biomarker in the screening of iron depletion in healthy children in high-income countries. However, ideally, reference ranges of iron status biomarkers should be based on studies showing that children with concentrations outside reference ranges have poor neurodevelopmental outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
2
9
0
1
Order By: Relevance
“…Reference intervals have been reported for newborns within 24 h, in a population of children between 6 months and 5 years, with a median of 4 years, and for infants during their fist 90 days (18)(19)(20)(21). A recent study compared Ret-He and soluble transferrin receptors (sTfR) for the diagnosis of iron depletion in young children aged 0.5-3 years, comparing these biomarkers with ferritin levels (22). The study showed that Ret-He was decreased at low levels of ferritin, and also that Ret-He level was significantly correlated with ferritin, MCV and Hb.…”
Section: Introductionmentioning
confidence: 99%
“…Reference intervals have been reported for newborns within 24 h, in a population of children between 6 months and 5 years, with a median of 4 years, and for infants during their fist 90 days (18)(19)(20)(21). A recent study compared Ret-He and soluble transferrin receptors (sTfR) for the diagnosis of iron depletion in young children aged 0.5-3 years, comparing these biomarkers with ferritin levels (22). The study showed that Ret-He was decreased at low levels of ferritin, and also that Ret-He level was significantly correlated with ferritin, MCV and Hb.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis requires various biomarkers to be examined, some of which lack clearly defined cutoff values [2,37]. In recent years, the diagnostic usefulness of sTfR and sTfR-F index has been recognized, and currently both parameters are included in diagnostic algorithms and clinical guidelines for ID, especially for the differential diagnosis of chronic anemia [32,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Infancy and childhood are periods of high prevalence of iron deficiency (ID) because of increased iron requirements for rapid growth [1][2][3][4][5]. Early detection of ID is essential in order to avoid adverse effects on development [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the first method, a SF cutoff < 15 μ g/L was used irrespective of the CRP level. In the second method, two different cutoffs were used for SF to take into account the absence (SF < 15 μ g/L) [ 30 ] or presence of inflammation (SF < 50 μ g/L) [ 6 ], which were defined as a CRP ≤ 5 mg/L or >5 mg/L, respectively [ 7 , 31 33 ].…”
Section: Methodsmentioning
confidence: 99%